THE IMPACT OF SUBJECTIVE NORMS, PERCEIVED BEHAVIOUR CONTROL AND ATTITUDE ON PURCHASE INTENTION OF THE CUSTOMERS OF TELECOMMUNICATION SECTOR - Yajid, Mohd Shukri Ab; Johar,; MGM, (International Journal of Psychosocial Rehabilitation, 2020)
The foremost purpose of current study is to examine the role of subjective norms, perceived behaviour control and attitude on the purchase intention of the customers of telecommunication companies of Malaysia. Data were collected form the managers of the customer relation and SPSS was used for analysis. The findings exposed that positive links among the subjective norms, perceived behaviour control and attitude with the purchase intention of the customers of telecommunication companies of Malaysia.